ANALYSIS OF THE DSN MUI FATWA ON SHARIA ELECTRONIC MONEY FROM THE PERSPECTIVE OF QIYAS (A STUDY ON LINKAJA SYARIAH APPLICATION) - Hardiyanti, Istiqom Shinta; Ahmad Agus Hidayat; Novita, Siska Arie; Sajiyo, Sajiyo (Universitas Islam Negeri Mataram, 2024)
This study aims to analyze the content of DSN MUI Fatwa No. 116/DSN-MUI/IX/2017 on Sharia electronic money from the perspective of qiyas, focusing on the case of the LinkAja Syariah application. The research method used in this study is descriptive qualitative, and the approach employed is library research. The findings of this study indicate that the LinkAja Syariah application is a development model of the LinkAja application designed to facilitate transactions while adhering to Sharia principles in its operational system. Similarly, the transactions follow the principles of cash payments and interbank transfers in Sharia banking, implementing Sharia financial principles. Thus, using the digital wallet application through LinkAja Syariah is legally permissible (mubah) as it fulfils the requirements and conditions of qiyas.